Detection of the Initiation Sequence Using EMF at the Yanacocha Mine in Perú. - Romel B. Villanueva (International Society of Explosives Engineers, 2025)
At the Yanacocha gold mine, in the Andes of northern Perú, the first instrumental tests were carried out in October 2019 to detect the initiation sequence of a production blast by detecting the EMF signal produced by the detonation from each blast hole in the sequence. Several experimental tests were carried out to choose the correct antenna and find the best setup of the high-speed Data Acquisition device (DAD) to detect these electromagnetic waves. Finally, the first measurement was obtained. With the instrument recording at a rate of 1 million samples per second, the initiation sequence was detected with 99.5% accuracy. It was found that it corresponded, without a doubt, to the designed scheme. The main result is that these tests provide us with a method and instrumentation to verify if the planned initiation sequence is carried out correctly in the field. In this way we can find operational deviations and detect possible misfires. This method has proven to be accurate, fast and easy to implement, mainly requiring an EMF signal capture equipment that can record at very high speed, something that is increasingly easier to satisfy with the development of microcontrollers. On the other hand, the type of antennas used in this method are low cost and very commercial. These tests have improved our understanding of the nature of detonation and have marked a new milestone in the development of blasting instrumentation in Peru.